PEMBERDAYAAN ANAK MUDA MELALUI KEWIRAUSAHAAN UNTUK MENCIPTAKAN SOLUSI INOVATIF - Susbiyani, Arik; Nursaid, Nursaid (UM Metro, 2025)
Â In an increasingly competitive global context, it is important for the younger generation to be equipped with entrepreneurial skills that can drive innovation and economic independence. MA Muhammadiyah I Andongsari is an educational institution that aims to produce a young generation that is not only academically intelligent, but also has practical skills that are relevant to the needs of society. With the shift in the economic paradigm towards entrepreneurship, this educational institution is expected to play an active role in creating innovative young entrepreneurs. The methods used in this empowerment include: Entrepreneurship Training, namely by holding a series of trainings on the basics of entrepreneurship, business management, and product marketing. Providing assistance to implement the ideas generated in the form of business ideas. The results of this activity show that there is an increase in knowledge of skills that include business planning, market analysis, and marketing. Participants succeeded in producing several innovative product ideas, for example handicraft products and processed foods. The creation of an entrepreneurial community among students as a forum for them to share information and ideas for business activities.Keywords: Empowerment, Entrepreneurship, Innovation